2012
DOI: 10.1080/01652176.2012.675634
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic tools to monitor udder health in dairy goats

Abstract: This article discusses the use of somatic cell count (SCC) and bacteriological culture (BC) as monitoring tools to assess the udder health situation of dairy goats. Both SCC and BC can be applied for milk samples from individual goats or at bulk milk samples. The causative agent of primary concern in the dairy goat industry is Staphylococcus aureus. This pathogen strongly increases goat milk SCC. The SCC is therefore a useful test to detect S. aureus-infected goats. However, several non-infectious factors, mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Routine diagnosis of mastitis is based on determining the concentration of somatic cells in milk, also known as SCC. While S. aureus IMI is often associated with chronic elevations in SCC in cows and small ruminants (Koop, Nielen, & van Werven, 2012;Paape et al, 2007;Schukken, Wilson, Welcome, Garrison-Tikofsky, & Gonzalez, 2003), this test is not specific for S. aureus IMI as many other bacteria can stimulate the same response. Hence, aetiological diagnosis is only possible based on detection of bacteria in aseptically collected milk samples from the mammary gland.…”
Section: Diagnosticsmentioning
confidence: 99%
“…Routine diagnosis of mastitis is based on determining the concentration of somatic cells in milk, also known as SCC. While S. aureus IMI is often associated with chronic elevations in SCC in cows and small ruminants (Koop, Nielen, & van Werven, 2012;Paape et al, 2007;Schukken, Wilson, Welcome, Garrison-Tikofsky, & Gonzalez, 2003), this test is not specific for S. aureus IMI as many other bacteria can stimulate the same response. Hence, aetiological diagnosis is only possible based on detection of bacteria in aseptically collected milk samples from the mammary gland.…”
Section: Diagnosticsmentioning
confidence: 99%
“…In dairy animals, SCC is an important milk characteristic possibly related to animal welfare. Research in dairy goats suggests that this indicator is related to intramammary infections, as SCC increases in presence of clinical or subclinical mastitis Koop et al, 2012), although the latter is asymptomatic and is not reported to affect goat welfare (Jimenez-Granado et al, 2014). Somatic cell count is routinely collected herd data on bulk milk; therefore, it is available in most farms.…”
Section: Absence Of Diseasementioning
confidence: 99%
“…As expected, the specificity of both markers decreased, but the steadier performances of CATH resulted in a specificity advantage of over 9 percentage points over SCC (82.98% for CATH versus 73.67% for SCC) at the same sensitivity of 91.80%, exemplified by the higher AUC of over 0.02. The advantage of CATH over SCC in late lactation ewes is particularly relevant since, as clearly pointed out by Koop et al [19], with all the due considerations linked to the prevalence of the disease, costs associated with false positive and false negative results, as well as species and contagiousness of intramammary pathogens circulating in the flock, higher specificity is preferable over higher sensitivity in mastitis detection.…”
Section: Discussionmentioning
confidence: 99%
“…Sheep can be screened for mastitis at the end of lactation, while goats should preferably be tested at peak lactation, as also suggested by others [19]. In late lactation sheep, CATH should be preferred over SCC for its higher specificity, but careful cost/benefit evaluations will have to be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation